Analisis Hubungan Saham Syariah Dan Sukuk Terhadap Pertumbuhan Ekonomi Indonesia Pada Tahun 2010-2019 - Sulistyo Wiky Aprianto; Rachma Indrarini (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
Investment plays a significant role in national economic growth. As of today, Islamic investment shows its growth every year, especially on Islamic stocks and Sukuk. This growth is believed to bring an impact on the national economy. This research aims to know the partial and simultaneous relations of Islamic stocks and Sukuk on Indonesia economic growth in 2010-2019. This is quantitative research. Classic assumption test, Pearson Product Moment Correlation Test and multiple correlation test are used in this research. This research shows that islamic stock and sukuk have both partial and simultaneous relations to Indonesia's economic growth in 2010 - 2019.